Textile yarn thermocouples for use in fabrics. (March 2019) - Hardianto, Hardianto; Malengier, Benny; De Mey, Gilbert; Van Langenhove, Lieva; Hertleer, Carla
Thermocouples are mainly used for accurate temperature measurements, but they can also be used for the generation of electric energy at low voltage and low power. If inserted into wearable garments, these thermocouples can be used to supply the electric energy required by portable electronic devices. The heat from the human body gives rise to a temperature gradient which can be converted into electric power. In this article, we study the possibility to create a thermocouple and thermopile from pure conductive textile yarns. Among the materials tested, nickel-coated carbon fiber in combination with stainless steel yarn, polypyrrole-coated carbon fiber, or carbon fiber has good potential to be a textile-based thermocouple. We also successfully made a 10-pair carbon fiber–nickel-coated carbon fiber junction thermopile from a single nickel-coated carbon fiber yarn by removing the nickel selectively through etching process.